Gender dan Ekonomi di Papua Barat - Evie Syalviana; Syahrul Syahrul (TASAMUH: Jurnal Studi Islam, 2021)
The role of Kokoda's woman in West Papua is very significant for helping the family economy. This paper attempts to explain and understand the role of Kokoda women in helping the needs of their families in Sorong City, West Papua. Using a qualitative approach, the writer tries to find data and facts in the field through observation and interview. So, the problems discussed in this paper are in accordance with the expected targets. The author found that Kokoda womens are one of Indonesian women as hard worker. They able to take on a dual role as wives and work outside the home, to help their husbands to fulfill their daily needs